PENGGUNAAN TANAMAN AREN PADA UPACARA SIPAHA LIMA MASYARAKAT PARMALIM - Z.N.A, Hanifah Mutia (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2018)
The purpose of this research are to know the beneficiaries and symbols contained in sugar palm plants in traditional ceremony Sipaha Lima. The method used in this research are the method of observation and depth interview. The data obtained in the form ofÂ plant parts used, how to obtain it and the meaning of symbol of the plant.The results is obtained eight types of use of sugar palm in traditional ceremony Sipaha Lima. Part of the plants used are: stems, leaves, and midrib. These plants are obtained from forests and crops.